From Continent to Ocean: Investigating the Multi-Element and Precious Metal Geochemistry of the Paraná-Etendeka Large Igneous Province Using Machine Learning Tools - J. J. Lindsay; H. S. R. Hughes; C. M. Yeomans; J. C. Ø. Andersen; I. McDonald (Earth Science, Systems and Society)
Large Igneous Provinces, and by extension the mantle plumes that generate them, are frequently associated with platinum-group element (PGE) ore deposits, yet the processes controlling the metal budget in plume-derived magmas remains debated. In this paper, we present a new whole-rock geochemical data set from the 135 Ma Paraná-Etendeka Large Igneous Province (PELIP) in the South Atlantic, which includes major and trace elements, PGE, and Au concentrations for onshore and offshore lavas from different developmental stages in the province, which underwent significant syn-magmatic continental rifting from 134 Ma onwards. The PELIP presents an opportunity to observe magma geochemistry as the continent and sub-continental lithospheric mantle (SCLM) are progressively removed from a melting environment. Here, we use an unsupervised machine learning approach (featuring the PCA, t-SNE and k-means clustering algorithms) to investigate the geochemistry of a set of (primarily basaltic) onshore and offshore PELIP lavas. We test the hypothesis that plume-derived magmas can scavenge precious metals including PGE from the SCLM and explore how metal concentrations might change the metal content in intraplate magmas throughout rifting. Onshore lavas on the Etendeka side of the PELIP are classified as the products of deep partial melts of the mantle below the African craton but without significant PGE enrichment. Offshore lavas on both continents exhibit similarities through the multi-element space to their onshore equivalents, but they again lack PGE enrichment. Of the four onshore lava types on the Paraná side of the PELIP, the Type 1 (Southern) and Type 1 (Central-Northern) localities exhibit separate PGE-enriched assemblages (Ir-Ru-Rh and Pd-Au-Cu, respectively). It follows that there is a significant asymmetry to the metallogenic character of the PELIP, with enrichment focused specifically on lavas from the South American continent edge in Paraná. This asymmetry contrasts with the North Atlantic Igneous Province (NAIP), a similar geodynamic environment in which continent-edge lavas are also PGE-enriched, albeit on both sides of the plume-rift system. We conclude that, given the similarities in PGE studies of plume-rift environments, SCLM incorporation under progressively shallowing (i.e., rifting) asthenospheric conditions promotes the acquisition of metasomatic and residual PGE-bearing minerals, boosting the magma metal budget.